A conceptual overview of ergonomics in construction industry / Asniza Hamimi Abdul Tharim ... [et al.] - Abdul Tharim, Asniza Hamimi; Jaffar, Noraidawati; Lop, Nor Suzila; Mohd Kamar, Izatul Farrita (2012)
The purpose of this paper is to give a conceptual overview of ergonomics in construction industry. The objective is to give a preliminary introduction and definition of ergonomics as applied in the construction industry. The study will include a brief introduction to the Malaysian construction industry, the history of ergonomics as well as the trades that are related to ergonomics in the construction process. The paper will also cover the result of ergonomics application in managing the effects of Musculoskeletal Disorders amongst construction workers. Ultimately, it is hoped that this research paper will be able to contribute towards a better understanding of an ergonomics overview in the construction industry.